Intestinal graft-versus-host disease is initiated by donor T cells distinct from classic cytotoxic T lymphocytes. - Thiele, D L (1989)
In these studies, the role of T helper and T cytotoxic cells in generating intestinal graft-vs.-host disease (GVHD) was examined. Treatment of C57BL/6J (B6) splenocytes with L-leucyl-L-leucine methyl ester (Leu-Leu-OMe) selectively removes natural killer cells, cytotoxic T lymphocyte (CTL) precursors, and the capacity to cause lethal GVHD in irradiated B6xDBA/2 F1 (B6D2F1) mice while preserving T helper cell function. Neither control nor Leu-Leu-OMe-treated DBA/2 donor spleen and bone marrow cells were found to induce lethal GVHD in B6D2F1 recipients. However, extensive colonic GVHD developed in B6D2F1 recipients of DBA/2 bone marrow and spleen cells. Enteropathic GVHD in DBA/2----B6D2F1 mice was reduced in severity after anti-L3T4 + C treatment of donor cells, and was eliminated by anti-Thy1.2 + C or the combination of anti-L3T4 and anti-Lyt2 + C treatment of the donor cell inoculum. However, neither anti-Lyt2 + C, Leu-Leu-OMe, nor anti-Lyt2 + C and Leu-Leu-OMe treatment of donor cells significantly decreased severity of gut GVHD. Leu-Leu-OMe treatment of DBA/2 or B6 SpC was comparably effective in preventing in vitro or in vivo generation of B6D2F1-specific CTL. These findings, therefore, demonstrate that histologically severe enteropathic GVHD does not require participation of CTL and is not always associated with high mortality rates.